VD_FINDINFO HC / 2012 / 265 vom 9. März 2012 - VD Tribunal cantonal (2012)
MITOYENNETÉ, MUR, TRAVAUX DE CONSTRUCTION, DÉLIMITATION DU TERRAIN | 9 CRF, 405 al. 1 CPC (CH), 108 al. 2 CDPJ, 166 al. 2 CDPJ